IMPROVEMENT OF LISTENING SKILL THROUGH DIRECTED LISTENING THINKING ACTIVITY (DLTA) LEARNING STRATEGY - Susanti Fuji Rahayu; Sukarno Sukarno; Sularmi Sularmi (Universitas Sebelas Maret, 2018)
The students listening skill are still low. The purpose of this research are: 1) to improve listening skill through DLTA for second grade students of State Primary School Tegalsari Number 60 Surakarta at 2017/2018 academic year, 2) to describe the improvement result listening skill for second grade students of State Primary School Tegalsari Number 60 Surakarta through DLTA learning strategy. The data collecting techniques used are observation, interview, documentation, and test. The data validity test use triangulation of sources and technique and content of validity. The data analysis techniques is interactive analysis model. The clasical mastery criteria for pre-cycle is up to 26,09% from 23 students achieved the minimal competences criteria (70). At the first cycle, the clasical mastery up 56,52% and at the second cycle up to 91,30%. Based on this research we can conclude that application Directed Listening Thinking Activity (DLTA) learning strategy can improve listening skill.